Polemic on Polri Reform: Where Do You Want the Police To Be Directed? - Edi Sahputra Hasibuan, Edi Sahputra Hasibuan (KRTHA BHAYANGKARA, 2025)
This paper examines the polemic surrounding the reform of the Indonesian National Police (Polri), which remains a key issue in the discourse on law enforcement and democracy in Indonesia. Since its separation from the Indonesian National Armed Forces (TNI) in 1999, the Indonesian National Police (Polri) was expected to become a professional, transparent, and accountable civilian institution. However, numerous cases of ethical violations, abuse of authority, and close ties to political power have resurfaced the fundamental question: where will Polri reform lead? This paper examines the background to the polemic, the cases that triggered the crisis of public trust, and the debate over the institutional position of the Polri, whether it should remain directly under the President or be moved into a ministerial structure. The research method used is a normative-empirical one . The normative approach is used to examine laws and regulations, particularly Law Number 2 of 2002 concerning the Indonesian National Police (Polri), as well as relevant internal Polri regulations. Meanwhile, an empirical approach is carried out by examining secondary data in the form of reports from independent institutions (Komnas HAM, Ombudsman, ICJR), court decisions related to cases involving police officers, and national and international media coverage. The analysis was conducted qualitatively and descriptively , outlining the phenomenon of violations, political dynamics, and civil society responses, and then linking these to theories of state institutional reform and legal principles. The analysis shows that structural change without accompanying cultural reform, a strong oversight system, and merit-based recruitment will only result in cosmetic reform. This article recommends strengthening external oversight, improving internal management, and orienting toward human rights-based policing as fundamental steps to answer the question "Where are we taking the police?" within the framework of a democratic state based on the rule of law.